IFC Financials 2015 : Private Sector Matters for Development - International Finance Corporation (Washington, DC: World Bank Group, 2015)
International Finance Corporation (IFC or the Corporation) is the largest global development institution focused on the private sector in developing countries. The accounting and reporting policies of IFC conform to accounting principles generally accepted in the United States (GAAP). IFC’s accounting policies are discussed in more detail in Section VI, Critical Accounting Policies, and in Note A to IFC’s Consolidated Financial Statements as of and for the year ended June 30, 2015 (FY15 Consolidated Financial Statements). Management uses Income available for designations (Allocable Income) (a non-GAAP measure) as a basis for designations of retained earnings. Allocable Income generally comprises net income excluding net unrealized gains and losses on equity investments and net unrealized gains and losses on non-trading financial instruments accounted for at fair value, income from consolidated entities other than AMC, and expenses reported in net income related to prior year designations.